2014
DOI: 10.1016/j.invent.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Guided internet-delivered cognitive behavior therapy for post-traumatic stress disorder: A randomized controlled trial

Abstract: The aim of this randomized controlled trial was to investigate the effects of guided internet-based cognitive behavior therapy (ICBT) for posttraumatic stress disorder (PTSD). Sixty-two participants with chronic PTSD, as assessed by the Clinician-administered PTSD Scale, were recruited via nationwide advertising and randomized to either treatment (n= 31) or delayed treatment attention control (n= 31). The ICBT treatment consisted of 8 weekly text-based modules containing psychoeducation, breathing retraining, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 43 publications
2
100
0
Order By: Relevance
“…Dropout rates from the study were comparable to previous trials of internet-based guided self-help for PTSD (Spence 2011, Ivarsson, Blom et al 2014) and other mental disorders (Spek, Cuijpers et al 2007). They were also of a similar magnitude to dropout from therapist-administered therapy ).…”
Section: Comparison To Other Studiessupporting
confidence: 73%
See 2 more Smart Citations
“…Dropout rates from the study were comparable to previous trials of internet-based guided self-help for PTSD (Spence 2011, Ivarsson, Blom et al 2014) and other mental disorders (Spek, Cuijpers et al 2007). They were also of a similar magnitude to dropout from therapist-administered therapy ).…”
Section: Comparison To Other Studiessupporting
confidence: 73%
“…In agreement with the findings of recent meta-analyses of internet-based self-help for PTSD, the intervention was found to be effective in comparison to waitlist (Kuester, Niemeyer et al 2016, Sijbrandij, Kunovski et al 2016, with the magnitude of effect lying at the higher end of the effect sizes reported by these reviews. The effect size was larger than that reported previously for internet-based CBT for clinical populations of PTSD sufferers (Spence 2011, Ivarsson, Blom et al 2014), which may be influenced by the fact that the intervention was systematically developed through an iterative process of modelling and pilot testing intended to create an optimally effective programme . The programme had a greater trauma-focus and emphasis on imaginal exposure work via writing and reading a narrative, than other internet-based CBT programmes for PTSD.…”
Section: Comparison To Other Studiesmentioning
confidence: 58%
See 1 more Smart Citation
“…The components were inspired and partly derived from previous Internet interventions for PTSD (Ivarsson et al 2014), based on prolonged exposure (Foa Frances & Davidson 1999) in combination with ideas from narrative exposure (Robjant & Fazel 2010). During a period of four weeks between the beginning of February and the beginning of March 2014, 56 women were self-recruited directly on the project-specific website (laura.iterapi.se).…”
Section: Design and Proceduresmentioning
confidence: 99%
“…We developed and tested a trauma-focused ICBT program focusing on childbirth as the traumatic event. The modules were built on evidence-based principles from trauma-focused CBT therapies (Foa, Frances & Davidson 1999;Robjant & Fazel 2010) and inspired and partly derived from previous ICBT projects for treatment of PTSD (Ivarsson et al 2014). …”
Section: Research Questionmentioning
confidence: 99%